Digital Skills for Communication of Government and Society on the Internet; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Meshcheryakova N. N. Nataliya Nikolaevna; Lukianova N. A. Natalia Aleksandrovna; Kiryanova L. G. Liliya Gennadievna; Ivchik A. A. Alyona Aleksandrovna (2016, 2016)
Title screen